Online Teaching and Learning at Primary School During COVID-19 Pandemic: Exploring Parents and Teachers' Voices - Rahmawaty Kadir (International Journal of Asian Education, 2022)
This study intends to explore Indonesian primary school teachers' and parents' perceptions of online learning and teaching in the COVID-19 pandemic situations. Particularly, this study intends to identify the significant challenges encountered by the Indonesian teachers and students' parents during the sudden shift of teaching and learning. Semi-structured interviews with a series of open-ended questions were used to collect information. Eleven teachers and students' parents from public high schools in Gorontalo province participated in this study. The results indicate that lack of technological devices and the cost of internet data connections are among the problems faced by teachers and parents. Ultimately, several recommendations were suggested for better action and successful implementation of online learning, particularly in underdeveloped areas in the eastern part of Indonesia.